The Implementation Of Accounting For Environmental Liabilities - Firmansyah, Amrie; Medina, Suhita Santi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
This study aims to discuss the accounting implementation by the Indonesia Companies in recognizing, measuring, presenting, and disclosing environmental obligations that occur as a result of the company's operations. The analysis is carried out by reviewing disclosures on environmental management activities that have been carried out by the company, which has financial reports and annual reports. The method used is descriptive qualitative method with the data used are secondary data, financial statements, and annual reports obtained from the official website of the Indonesia Stock Exchange from 2015 to 2017 fiscal years. The samples employed in this study is thirteen food and beverage subsector companies listed on the Indonesia Stock Exchange from 2015 to 2017. The results of this study suggest that from 2015 to 2017, the food and beverage sub-sector companies have not reported any environmental obligations in the form of social-environmental responsibilities in the financial statements. The companies report their environmental responsibility activities as a company expense reported on the income statement. Accounting for environmental obligations related to recognition, measurement, recording, disclosure, and reporting has not been regulated in financial accounting standards, so reporting environmental obligations is still voluntary.